Socio-Digital Hybridity in Disaster Preparedness: A Study of Community-Based Communication Practices in the Merapi Highlands - Past Novel Larasaty; Muhammad Hidayat (Jogjakarta Communication Conference (JCC), 2026)
Community-based communication practices (CBCP) represent a pivotal shift from top-down, technocratic dissemination models toward participatory, dialogic frameworks that prioritize local knowledge and social capital. This research examines the dynamics of CBCP within the context of disaster mitigation on the slopes of Mount Merapi, specifically in the Sleman Regency of Yogyakarta, Indonesia. As one of the most active volcanoes globally, Mount Merapi presents a continuous threat that necessitates robust, decentralized communication systems to ensure community resilience. Utilizing a qualitative case study approach, this study analyzes the integration of traditional communication tools, such as the kentongan (bamboo slit drum), with modern digital platforms like WhatsApp and community radio. The investigation further evaluates the Sister Village (Desa Persaudaraan) program as a formalized model of participatory communication management. Data was gathered through in-depth interviews with officials from the Yogyakarta Provincial Disaster Management Agency (BPBD DIY), focus group discussions with community leaders and disaster volunteers, participatory observation, and secondary data analysis. The findings indicate that effective disaster communication in Merapi is not merely a product of technological infrastructure but is deeply rooted in social capital, specifically bonding and bridging ties, that foster mutual trust and collective action. A four-quadrant communication framework articulated by institutional informants reveals that community knowledge, monitoring capacity, information dissemination, and response readiness constitute the foundational architecture of regional resilience. However, challenges persist regarding gender representation in strategic leadership and the financial sustainability of community-led media. This study contributes to the third paradigm of development communication by demonstrating how grassroots-led communication contracts and informal social networks constitute the foundational infrastructure of regional resilience.